(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Milk products contain important nutrient elements and are mostly consumed in developing countries. Good quality control is very essential in the production and processing of powdered milk products, also transportation and storage conditions might have effects on composition of these products. The deficiency or excess of any of the mineral elements in powdered milk may create significant health problems for the consumer. In this study, the concentration levels of some mineral elements in different brands of powdered milk sold in India were determined using Atomic Absorption Spectrometer (AAS). The calcium, iron and zinc concentrations have been found higher in powdered milk samples in comparison of pasteurised milk samples.